Miniaturised microstrip antenna using high-impedance wires incorporating AMC MTMs. Issue 4 (1st October 2016) - Jafargholi, Amir; Khani, Milad Mohamad
ABSTRACT: In this article, a new miniaturised microstrip gap proximity-fed patch antenna, using high-impedance wire (HIW), is proposed. To overcome the slot length problem in HIW structure, capacitively loaded loops (CLLs) is incorporated, which leads to miniaturised efficient antenna. This new design is much more compact than previous designs, making it easier to use in commercial applications. A prototype of the proposed antenna is fabricated and tested. The CST simulation results show good agreement with measurements. Measurement shows that the size of the antenna reduced while the maximum gain and radiation efficiency are both close to theoretical limits.